Aluminum Material as a Solution to Create Strong and Lightweight Combat Vehicles with Increased Efficiency from Fuel Savings - Napitupulu, Jofim Yordaniel; Murniati, Riri; Hirawan, Agung; Wijanarko, Fakhri; Alwan, Mochammad Ibnu (MUNISI: Military Mathematics and Natural Sciences, 2025)
In the current era, combat vehicles are required for strong defense, extensive expedition, agile or nimble and lethal, with greater ability to conduct special operations. One of the problems in combat vehicles is their weight which makes a significant factor in their ability to achieve endurance with agility and speed. Some research shows that aluminum material is the solution to overcome the weight and durability of combat vehicles. Research shows how the determination of aluminum material in general can greatly save fuel when the mass is reduced from 0-15%. From this research, we hope to open people’s minds, that the importance of specifying the material used for military vehicles by improving vehicle functions in terms of speed, strength, and fuel efficiency.